Challenging Moral Attitudes With Moral Messages. (August 2019) - Luttrell, Andrew; Philipp-Muller, Aviva; Petty, Richard E.
When crafting a message, communicators may turn to moral rhetoric as a means of influencing an audience's opinion. In the present research, we tested whether the persuasiveness of explicitly moral counterattitudinal messages depends on how much people have already based their attitudes on moral considerations. A survey of the literature suggests several competing hypotheses that we tested across two studies. The results support a persuasive-matching pattern: A moral appeal was more persuasive than a nonmoral appeal to the extent that initial attitudes were based on moral concerns (i.e., attitudes were moralized), but the opposite was true when initial attitudes had less of a moral basis. Exploratory analyses also showed that these effects were mediated by valenced thoughts about the message and moderated by political orientation. These findings add new insight to literatures on both the effects of moral arguments and moralized attitudes.